The difference in flow pattern, heat transfer and pressure drop characteristics of mini-channel flow boiling in horizontal and vertical orientations - Saisorn, Sira; Wongpromma, Pakorn; Wongwises, Somchai (My University, 2018)
Flow pattern, heat transfer, and pressure drop data for different flow orientations was presented in this study. The data was obtained based on flow boiling experiments with R-134a flow through a 1 mm diameter channel which was aligned in different orientations, i.e. horizontal flow, vertical upward flow, and vertical downward flow. A constant surface heat flux condition was performed under a saturation pressure of 8 bar, a heat flux range of 1–60 kW/m2, and a mass flux range of 250–820 kg/m2s. The experimental results showed the importance of the change in the flow direction. The shape of the gas slug during horizontal flow did not look the same as in the vertical orientations. Heat transfer coefficient and pressure drop became increased when the refrigerant flowed in the vertical downward direction. The experimental data was also compared with the existing prediction methods.
Keywords: Flow boiling; Flow pattern; Heat transfer; Mini-channel; Pressure drop